1980
DOI: 10.1007/bf01542792
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale isolation of UV-sensitive clones of CHO cells

Abstract: We have isolated 54 ultraviolet light (UV) sensitive clones of Chinese hamster ovary (CHO) cells, including two from a parent cell line which is hypersensitive to ethyl methanesulfonate (EMS) and is also sensitive to X rays. A replica plating technique was used for the isolation of two of the clones, and a semiautomated technique was used for the isolation of the other 52 clones. We have observed UV sensitization of up to 5-fold in the mutants relative to the parent in terms of the slopes of the survival curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
0

Year Published

1984
1984
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(41 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…The human cells were grown in suspension culture at 37°C in RPMI 1640 medium supplemented with 10% fetal calf serum. The Chinese hamster ovary (CHO) cell line AA8 and a cell line (EU2) derived from it with mutations in both the ERCC-J and the XRCC-1 genes were obtained from the collection of D. Busch (5). The CHO lines were grown in roller bottles in Dulbecco's minimal essential medium supplemented with 10% fetal calf serum.…”
Section: Materuils and Methodsmentioning
confidence: 99%
“…The human cells were grown in suspension culture at 37°C in RPMI 1640 medium supplemented with 10% fetal calf serum. The Chinese hamster ovary (CHO) cell line AA8 and a cell line (EU2) derived from it with mutations in both the ERCC-J and the XRCC-1 genes were obtained from the collection of D. Busch (5). The CHO lines were grown in roller bottles in Dulbecco's minimal essential medium supplemented with 10% fetal calf serum.…”
Section: Materuils and Methodsmentioning
confidence: 99%
“…Our results showed that AA8-4 DNA-treated cells gave 4 positives out of 14 total samples (in 11 experiments) versus 0 positives out of 12 samples (in 8 experiments) with UV-135 DNA-treated cells ( Table 2). The differences between the two DNA treatments in number and proportion of positive samples were very significant, either by the chi-square test (P = 0.044) or by the more appropriate binomial test for proportion of positives (P = 0.018).…”
mentioning
confidence: 65%
“…The molecular identification of a possible human ER gene complementing the XP-A genotype has been reported previously (23). However, several technical difficulties with the use of XP cell lines for this type of experiment have made another mammalian cell system attractive for repair gene transfer.The availability of ER-proficient CHO cells and the technical advantages of genetic manipulation in this system led to the isolation of a large series of recessive, UV-sensitive (UV') mutants which fall into five complementation groups (4,(25)(26)(27). These mutants were derived from CHO clone AA8-4, which is ER proficient by criteria of UV repair incision (4.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of different UV-sensitive mutants have been generated from established cell lines (5,15,23,25,27,30,34). One of these mutant lines, UV-20, isolated from a parental Chinese hamster ovary (CHO) cell line, is sensitive to a number of other DNA-damaging agents, including the DNA cross-linking agent mitomycin C (MM-C) (29).…”
mentioning
confidence: 99%